Political Ideology, Defection and Electoral Outcomes in Nigeria: Exploring the Intricacies and Realities (Journal of Management and Social Sciences, 2024)
AbstractPoverty of ideology and its attendance conflict have been of dramatic effect not only on political party, but also on the outcome of election, national integration and sustainable development. In about the last twenty years, Nigerian democracy has witnessed series of political defections with politicians decamping from one political party to the other particularly from opposition parties to the ruling party. However, it has been perceived that political parties in Nigeria portend a vehicle of political utility bereaved of ideology and deficit in both ideas and principle. This study, therefore, anchored on rational choice theory, explored the intricacies of political ideology in Nigeria political space. Using content analysis of secondary data obtained from various available literature and documentary evidences, and descriptive analysis of primary data obtained through the administration of questionnaire on purposively selected respondents, this study critically explored the linkage between party ideology and electoral outcomes in Nigeria. It was found that political parties in Nigeria are not ideological based, and as such, are only interested in gaining power at all cost. The result of the findings revealed that there was a strong connection between party ideology and defection on electoral outcomes in Nigeria’s Fourth Republic and thus recommended that the activities of all political parties in Nigeria should be guided by definite ideologies, programmes and policies that defines their vision for a better Nigeria.Keywords Defection, democracy, electoral outcome, political ideology, political party